The Implication of Attitude Towards Educational Support System (ESS) Use in Education - Suka, Intan Emilya; Abdul Hamid, Norhadilah (Research in Management of Technology and Business, 2020)
The information transmission through advancement of personal computer and its application should be possible higher, quicker, and friendlier. There are expanding in number of new advances and programming that can be utilized for instructive reason. Through Educational Support System (ESS), exercises, for example, procuring, arranging, conveying, delivering, advancing, displaying should be possible as it give a variety of apparatuses and assets. ESS can be expected as help to college and instructors as it likewise helps in achieve the destinations of educating. Furthermore, ESS can make learning procedure and research increasingly powerful by preparing data materials required for address planning and explore and give innovations expected to the creation, duplication, refreshing and conveyance of address easily. While, the current literature focuses on the users’ continuance satisfaction, perception towards technology, intention to utilize ESS and the effectiveness of ESS, there is comparative lack of research on the impact of attitude towards ESS use in education. Hence, the current study adopted Technology Adoption Model to investigate the attitude among Universiti Tun Hussein Onn Malaysia (UTHM) lecturers. This paper aim to identify the relationship between attitudes towards ESS use in education. The study employed random sampling method and quantitative research design. For quantitative analysis, data collected through online survey questionnaire and the questionnaire is adopted from previous study. The expected outcome of the research is there is positive relationship between attitudes towards ESS use in education.